Changes in mining‐induced seismicity before and after the 2007 Crandall Canyon Mine collapse. Issue 6 (4th June 2014) - Kubacki, Tex; Koper, Keith D.; Pankow, Kristine L.; McCarter, Michael K.
Abstract On 6 August 2007, the Crandall Canyon Mine in central Utah experienced a major collapse that was recorded as an Mw 4.1 seismic event. Application of waveform cross‐correlation detection techniques to data recorded at permanent seismic stations located within 30 km of the mine has resulted in the discovery of 1494 previously unknown microseismic events related to the collapse. These events occurred between 26 July 2007 and 19 August 2007 and were detected with a magnitude threshold of completeness of 0.0, about 1.6 magnitude units smaller than the threshold associated with conventional techniques. Relative locations for the events were determined using a double‐difference approach that incorporated absolute and differential arrival times. Absolute locations were determined using ground‐truth reported in mine logbooks. Lineations apparent in the newly detected events have strikes similar to those of known vertical joints in the mine region, which may have played a role in the collapse. Prior to the collapse, seismicity occurred mostly in close proximity to active mining, though several distinct seismogenic hot spots within the mine were also apparent. In the 48 h before the collapse, changes in b value and event locations were observed. The collapse appears to have occurred when the migrating seismicity associated with direct mining activity intersected one of the areas identified as a seismic hot spot. Following the collapse, b values decreased and seismicity clustered farther to the east.